Axonal injury detected by in vivo diffusion tensor imaging correlates with neurological disability in a mouse model of multiple sclerosis - Budde, Matthew D.; Kim, Joong Hee; Liang, Hsiao-Fang; Russell, John H.; Cross, Anne H.; Song, Sheng-Kwei (NMR in biomedicine, 2008)
Recent studies have suggested that axonal damage, and not demyelination, is the primary cause of long‐term neurological impairment in multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis (EAE). The axial and radial diffusivities derived from diffusion tensor imaging have shown promise as non‐invasive surrogate markers of axonal damage and demyelination, respectively. In this study, in vivo diffusion tensor imaging of the spinal cords from mice with chronic EAE was performed to determine if axial diffusivity correlated with neurological disability in EAE assessed by the commonly used clinical scoring system. Axial diffusivity in the ventrolateral white matter showed a significant negative correlation with EAE clinical score and was significantly lower in mice with severe EAE than in mice with moderate EAE. Furthermore, the greater decreases in axial diffusivity were associated with greater amounts of axonal damage, as confirmed by quantitative staining for non‐phosphorylated neurofilaments (SMI32). Radial diffusivity and relative anisotropy could not distinguish between the groups of mice with moderate EAE and those with severe EAE. The results further the notion that axial diffusivity is a non‐invasive marker of axonal damage in white matter and could provide the necessary link between pathology and neurological disability. Copyright © 2007 John Wiley & Sons, Ltd.